P278 Transcranial direct current stimulation (tDCS) as treatment for major depression (DepressionDC) – Objectives and design of a prospective multicenter double blind randomized placebo controlled trial. Issue 3 (March 2017) - Kumpf, U.; Palm, U.; Nolden, J.; Pfeiffer, A.; Egert, S.; Görlitz, T.; Bajbouj, M.; Plewnia, C.; Langguth, B.; Zwanzger, P.; Kirsch, B.; Worsching, J.; et al.
Abstract : Objectives: Transcranial Direct Current Stimulation (tDCS) is considered as a putative therapeutical approach in Major Depressive Disorder (MDD) allowing for a non-invasive modulation of dysregulated frontal activity (Kalu et al., 2012). Findings of the largest 2 × 2 factorial randomized controlled trial (RCT) in MDD to date suggest an antidepressant effect of tDCS combined with a Selective Serotonin Reuptake Inhibitor (SSRI; Sertraline) that is superior to placebo treatment, tDCS alone and sertraline alone (Brunoni et al., 2013). With regard to a possible introduction of tDCS as treatment option for MDD a methodological sound replication trial is needed. Moreover, this study should overcome limitations of the previous trial (2 × 2 factorial design with small sample size; short treatment period; monocentre study). Methods: In this randomized, placebo-controlled multicenter trial patients with MDD receive a 6-weeks treatment with prefrontal tDCS (anode over electrode position F3, cathode over F4, 5 sessions/week for 4 weeks followed by 2 sessions/week for 2 weeks, 30 min/day, 2 mA intensity) or sham tDCS (frequency and duration correspondent to active tDCS, ramp in and ramp out only without intermittent stimulation), as adjunctive treatment with a SSRI. Follow-up per patient is 3 and 6 months after the last tDCS session. Before, during, and after the treatment period different assessment scales will be conducted using a tablet-PC program which is specifically designed for this study to record neuropsychological features and the course of the individual symptomatology. Additionally, patients receive optional investigations including functional magnetic resonance imaging (fMRI) measuring functional and structural connectivity at baseline, after 6 weeks of tDCS treatment and 12 weeks after the last tDCS session. Discussion: The purpose of this study is to explore the sustained efficacy and tolerability of repeated tDCS for the treatment of MDD and to assess the long-term efficacy of tDCS over 3–6 months. It is hypothesized that prefrontal tDCS in combination with an SSRI will provoke an antidepressant effect while antidepressant medication alone (sham tDCS) did not. This will be measured by the change from baseline in the Montgomery-Åsberg Depression Rating Scale scores after 6 weeks of treatment.